Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai ASN pada Kantor Kecamatan Tanon Kabupaten Sragen - Nelly Eka Pratiwi; Sutarno (ARZUSIN, 2026)
Improving the performance of the State Civil Apparatus (ASN) is necessary to support the quality of public services, particularly by strengthening work motivation and work discipline. This study aimed to analyze the effects of work motivation and work discipline on the performance of ASN employees at the Tanon Subdistrict Office, Sragen Regency. The study employed a quantitative approach using a survey method. The study population consisted of 35 ASN employees, all of whom were included in the sample using saturated sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression after validity, reliability, normality, multicollinearity, and heteroscedasticity tests had been conducted. The results showed that work motivation had a positive and significant effect on employee performance, with a regression coefficient of 0.618, a test statistic of 5.899, and a significance value of less than 0.001. Work discipline also had a positive and significant effect on employee performance, with a regression coefficient of 0.376, a test statistic of 4.041, and a significance value of less than 0.001. The adjusted coefficient of determination (adjusted R²) of 0.520 indicated that work motivation and work discipline explained 52.0% of the variation in employee performance, while the remaining 48.0% was explained by factors outside the research model. This study concludes that work motivation and work discipline are important factors in improving the performance of ASN employees. These findings imply the need to provide recognition, opportunities for self-development, organizational support, supervision, and consistent enforcement of regulations to strengthen employee performance and the quality of public services.